Biopsychosocial Determinants of Human Papilloma Virus Immunization in Women of Reproductive Age in Surakarta, Central Java - Gabriela Advitri Febriani; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Cervical cancer ranks second as the cause of death in women worldwide. Cervical cancer is preventable by Human Papilloma Virus (HPV) immunization. It was hypothesized that use of HPV immunization is determined by biopsychosocial factors as involved in the Health Belief Model and Social Learning Theory. This study aimed to analyze the determinants of HPV immunization use in women of reproductive age.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at Permata Harapan Clinic and Budi Sehat Laboratory Clinic, Surakarta, Central Java. The data were collected from February to March 2018. A sample of 200 women was selected by random sampling, consisting of 50 women undertaking screening and 150 women not undertaking screening. The dependent variable was HPV immunization. The independent variables were perceptions of susceptibility, seriousness, benefit, barrier, respectively, and self-efficacy, education, family income, employment status, family support, social environment, and cervical cancer screening. Data on HPV vaccine use were taken from medical record. The data were collected by questionnaire and analyzed by path analysis.Results: Use of HPV immunization was directly associated with perceived susceptibility (b= 2.01; 95% CI= 1.03 to 3.00; p<0.001), perceived seriousness (b= 1.52; 95% CI 95%= -0.08 to 3.13; p=0.063), self efficacy (b= 1.55; 95% CI= 0.05 to 3.05; p=0.043), and perceived barrier (b= -2.25; 95% CI= -3.22 to -1.28; p<0.001). It was indirectly associated with perceived benefit, education, family income, employment status, family support, social environment, and cervical cancer screening.Conclusion: Use of HPV immunization is directly associated with perceived susceptibility, perceived seriousness, self-efficacy, and perceived barrier. It is indirectly associated with perceived benefit, education, family income, employment status, family support, social environment, and cervical cancer screening.